Biogas Production from Corn Stover by Solid-State Anaerobic Co-digestion of Food Waste - Lukhi Mulia Shitophyta; Gita Indah Budiarti; Yusuf Eko Nugroho; Dika Fajariyanto (Politeknik Negeri Malang, 2020)
Biogas has become an alternative fuel to reduce the lack of fossil fuel. Biogas can be produced from organic wastes such as corn stover. Corn stover is a typical lignocellulosic biomass and contains a total solid (TS) content higher of 15%. Biogas production was conducted by solid-state anaerobic digestion with addition co-digestion of food waste. Co-digestion is useful to help the digestion of corn stover. The purposes of this study were to investigate the effect of the percentage of food waste, volatile solid (VS) reduction, and kinetic model on biogas production from corn stover. Results showed that food waste had a significant effect on biogas yield (p < 0.05). The highest biogas yield of 584.49 mL g-1 VS-1 and the highest VS reduction of 40% was obtained at food waste of 20%. The kinetic model of biogas production from corn stover and food waste followed the first-order kinetic model.